Communication barriers between local contractors and foreign unskilled labour / Muhamad Farhan Rosli and Kharizam Ismail - Rosli, Muhamad Farhan; Ismail, Kharizam (2018)
Over the past few years, the number of foreign labour has increased tremendously due to vast development of the country’s economy. However leads to a new problem which is in aspects of communication barriers between local contractors and foreign unskilled labour. Hence, this issue comes out with an aim f the research which is to identify the method of local contractor in order to manage the communications barrier towards foreign unskilled labour. The objectives are to identify the factors of communication barriers, to investigate the effects from communication barriers and to explore the approach of the local contractors that can be used to solve the communication barrier. A quantitative approach was used in this research and a questionnaire was used as the instrument which was distributed to the local contractors from G5. The outcomes of this research found that the highest factor was due to insufficient knowledge of the local language as foreign labours’ fluency level depends mostly on years of experience living in the country. This is regarded as a huge problem as total miscommunication could even cause accidents to happen in the construction site. Therefore, the best solution to overcome this problem is by conducting local language training classes for foreign unskilled labour by Construction Industry Development Board (CIDB). The result of this research will help the local contractors in order to overcome the communication barriers towards foreign unskilled labour.